PENGEMBANGAN PERANGKAT PEMBELAJARAN MATERI TATA SURYA UNTUK MENGOPTIMALKAN PEMANFAATAN MEDIA VIDEO BERBASIS KOMPUTER - Ide Lia Marzuki; Agus Suyatna; I Dewa Putu Nyeneng (Jurnal Pembelajaran Fisika, 2013)
Research and development carry out in order to find out study of scenario to optimize the utilization of video solar system and to know the student worksheet to be balance with used video of solar system than find through result of this. Research population includes all student from class IX of junior high school 19 in Bandar Lampung. The examples as a small group test student class IX G. The research data gathered by observation, direct interview, expert test, and questioner. The development conducted by modifying the development model of Borg and Gall includes analyzing early product of Development, testing expert, product revision, and field-testing. On the development stage learning data of solar system on class IX to be optimize with video media based of computer such as syllabus, teaching plan, and student worksheet adopted with video media. After words on the expert testing phase, revision will be conducted by researches to find any mistakes or discrepancy from the result of the product using assessment to expert test. Then improvement will be executed base on the advise from test expert. The last step would be the field test which conducted to 32 students The result of the field test showed that level of student learning is 78.13% with a value of 70 KKM. The final level is more than 75% so that the learning can be effective.Key Words : Development, Learning equipment and Video media.